The Finnmarkian Orogeny revisited: An isotopic investigation in eastern Finnmark, Arctic Norway - Kirkland, Chris; Daly, J.; Chew, D.; Page, L. (2008)
The Scandinavian Caledonides have been viewed as resulting from either a single Silurian (i.e. Scandian) event or from polycyclic orogenies involving several collisions on the margin of Baltica. Early studies of the Kalak Nappe Complex (KNC) in Finnmark, Arctic Norway, led to the hypothesis of an Early Cambrian-Early Ordovician (520-480 Ma) Finnmarkian Orogeny, though the nature of this tectonic event remains enigmatic. In this contribution we have employed in situ UV laser ablation Ar-Ar dating of fine-grained phyllite and schist from the eastern Caledonides of Arctic Norway to investigate the presence of pre-Scandian tectonometamorphic events. U-Th-Pb detrital zircon and whole rock Sm-Nd analyses have been used to test the regional stratigraphic correlations of these metasedimentary rocks. These results indicate that the Berlevåg Formation within the Tanafjord Nappe, previously assumed to be part of the KNC, was deposited after 1872 Ma and prior to a low temperature hydrothermal event at 555 ± 15 Ma. It has a likely provenance on the Baltica continent, lacks any Grenville-Sveconorwegian detrital zircons, and thus cannot be part of the KNC which contains abundant detritus in this age range. Instead the Berlevåg Formation is interpreted as part of the Laksefjord Nappe Complex, which structurally underlies the KNC. Laser-ablation argon-argon dating also shows that late Caledonian (i.e. Scandian) tectonometamorphism affected both the KNC and its immediate footwall at c. 425 ± 15 Ma. This is corroborated by a step-heating argon-argon muscovite age of 424 ± 3 Ma which is interpreted as dating cooling. However, within two samples from the KNC, an earlier (Middle-Late Cambrian) metamorphic event is also recorded. A biotite-grade schist yielded an Ar-Ar inverse isochron age of 506 ± 17 Ma from whole rock surfaces, in which the mineral domains are too fine-grained to date individually. An early generation of muscovite from a coarser-grained amphibolite-facies sample yielded an inverse isochron of 498 ± 13 Ma. Both isochron ages have atmospheric argon intercept values. Previous studies have documented similar Cambrian ages in the Caledonian nappes below the KNC. These results suggest correlative tectonometamorphic events in the eastern KNC and its footwall at c. 500 Ma. This Cambrian event may reflect the arrival of the Kalak Nappe Complex as a previously constructed exotic mobile belt onto the margin of Baltica. Combined with recent studies from the western Kalak Nappe Complex, the results do not support the traditional constraint on the Finnmarkian Orogeny sensu stricto. However they vindicate classic tectonic models involving a Cambrian accretion event. © 2008 Elsevier B.V. All rights reserved.